2021
DOI: 10.1021/acsnano.0c08357
|View full text |Cite
|
Sign up to set email alerts
|

Modified MAX Phase Synthesis for Environmentally Stable and Highly Conductive Ti3C2 MXene

Abstract: Figure S1. (a) Blocks of Ti3AlC2 (top) and Al-Ti3AlC2 (bottom), (b) mass loss during the washing of Al-Ti3AlC2 with HCl, (c) image of the purple filtrate from the acid washing process, (d) Al-Ti3AlC2 particles after acid washing using HCl, (e) higher magnification of (d).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
445
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 577 publications
(459 citation statements)
references
References 38 publications
14
445
0
Order By: Relevance
“…[11] More recently, Ti 3 C 2 T x MXene with better oxidation resistance was fabricated from Al-rich Ti 3 Al x C 2 precursor with higher crystallinity. [12] Nevertheless, there is still a lack of immediately commercializable ways for low-cost and environmentally sustainable storage of MXenes in long term.…”
mentioning
confidence: 99%
“…[11] More recently, Ti 3 C 2 T x MXene with better oxidation resistance was fabricated from Al-rich Ti 3 Al x C 2 precursor with higher crystallinity. [12] Nevertheless, there is still a lack of immediately commercializable ways for low-cost and environmentally sustainable storage of MXenes in long term.…”
mentioning
confidence: 99%
“…Another application of MAX phase coating ( Akter et al., 2020 ) recommends that Hf 2 SN and Hf 2 Sc are good candidates to decrease solar heating. A recent study shows the problem of MXenes , the rate at which MXenes oxidize and degrade as stored as an aqueous suspension ( Mathis et al., 2021 ). The experiment suggested that adding excess aluminum, Al, during synthesis leads to improved crystallinity of M Xene that can exhibit an increased shelf life ten times.…”
Section: Resultsmentioning
confidence: 99%
“…Since their discovery, more than 30 stoichiometric MXene structures have been synthesized, but the expanded research on MXene and their application in various fields requires additional investigations on improving the MXene quality and their functional performances [ 67 ]. In the case of sensing applications, synthesis not only controls the material’s morphology but also directly affects sensory functions, and therefore, new synthesis routes shall be explored and process parameters shall be adjusted.…”
Section: Mxenes—novel Two-dimensional Compoundsmentioning
confidence: 99%